LEGAL PROTECTION FOR CONSUMERS AS VICTIMS OF SWAB/PCR TESTS BASED ON REGULATION NO. 8/1999 REGARDING CONSUMER PROTECTION - Dewangga, Raditya Aufar; Hartantien, Sinarianda Kurnia (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
In the pandemic era, it is clear that compliance with procedures is essential and has a significant impact on ending the pandemic. Besides wearing masks and maintaining social distancing, routine testing to detect the virus—such as antigen tests—is also necessary. This requirement is based on the Minister of Health’s Decree No. 234/2020, issued on April 7, 2020, which mandates all laboratories in Indonesia to implement early identification and report results to the local Health Office. However, this situation has led to a new form of crime that indirectly violates consumer rights through the falsification of test results by service providers. In similar cases, legal discussions often focus on criminal liability, while consumer rights and protections are also at stake. This study examines the legal protection available to consumers affected by fake SWAB/PCR tests, as well as the government’s responsibilities and efforts in ensuring legal protection for those harmed. The research employs a Juridical-Normative approach, utilizing secondary legal materials with statutory and case-based analysis. A descriptive-analytical specification is used to address the research problem as defined by the researchers.